Phononic thermal conductivity in silicene: the role of vacancy defects and boundary scattering. (22nd March 2018) - Barati, M; Vazifehshenas, T; Salavati-fard, T; Farmanbar, M
Abstract: We calculate the thermal conductivity of free-standing silicene using the phonon Boltzmann transport equation within the relaxation time approximation. In this calculation, we investigate the effects of sample size and different scattering mechanisms such as phonon–phonon, phonon-boundary, phonon-isotope and phonon-vacancy defect. We obtain some similar results to earlier works using a different model and provide a more detailed analysis of the phonon conduction behavior and various mode contributions. We show that the dominant contribution to the thermal conductivity of silicene, which originates from the in-plane acoustic branches, is about 70% at room temperature and this contribution becomes larger by considering vacancy defects. Our results indicate that while the thermal conductivity of silicene is significantly suppressed by the vacancy defects, the effect of isotopes on the phononic transport is small. Our calculations demonstrate that by removing only one of every 400 silicon atoms, a substantial reduction of about 58% in thermal conductivity is achieved. Furthermore, we find that the phonon-boundary scattering is important in defectless and small-size silicene samples, especially at low temperatures.